1997
DOI: 10.30843/nzpp.1997.50.11275
|View full text |Cite
|
Sign up to set email alerts
|

Feeding by <i>Sitona discoideus</i> after exposure to the parasitoid <i>Microctonus aethiopoides</i>

Abstract: The impact of the parasitoid Microctonus aethiopoides Loan (Hymenoptera: Braconidae) on the feeding activity of its adult weevil host Sitona discoideus Gyllenhal (Coleoptera: Curculionidae) was studied in the laboratory. Feeding by parasitised S. discoideus showed a distinct pattern with no significant feeding during the first two days after exposure to the parasitoids, peak feeding six days before parasitoid emergence and no feeding on the day of parasitoid emergence. Reproductive female S. discoideus consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…While there was a signifi cant relationship between weevil size and the amount of foliage ingested in the outdoor experiment, it appeared that the interaction between clover cultivar and weevil sex was also important in determining feeding rate. Reproductive females are likely to be voracious, as Evans et al (1997) had found reproductive S. discoideus females consumed about four times more foliage than males and non-reproductive females. However, the reason why females appeared to eat more Prestige and the males Kopu are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…While there was a signifi cant relationship between weevil size and the amount of foliage ingested in the outdoor experiment, it appeared that the interaction between clover cultivar and weevil sex was also important in determining feeding rate. Reproductive females are likely to be voracious, as Evans et al (1997) had found reproductive S. discoideus females consumed about four times more foliage than males and non-reproductive females. However, the reason why females appeared to eat more Prestige and the males Kopu are unclear.…”
Section: Discussionmentioning
confidence: 99%